Effect of organic solvents treatment on structure of chitin and its enzymatic hydrolysis. (April 2022) - Zhou, Ning; Yang, Pengfan; Chen, Jie; Wei, Guoguang; Wang, Chengyong; Zhang, Alei; Chen, Kequan; Ouyang, Pingkai
Highlights: A cocktail of chitinolytic enzymes was developed to efficiently produce GlcNAc from chitin. Chitin pretreated by three organic solvents exhibited 4.90–8.21-fold hydrolysis efficiency better than raw chitin. The alter chitin structure without deacetylation resulted in the increased hydrolysis efficiency. GlcNAc with a purity of 96% were obtained from organic solvent pretreated chitins. Abstract: In this study, the effect of pretreatment with three organic solvent systems on enzymatic hydrolysis of chitin was investigated. Firstly, genes coding three chitinolytic enzymes Cm Chi1, Cm Chi4, and Cm NAGase from Chitinolyticbacter meiyuanensis SYBC-H1 were cloned and functionally expressed. Then, a cocktail capable of producing GlcNAc from chitin was formulated with 71.4% recombinant Cm Chi1, 23.8% recombinant Cm Chi4, and 4.8% recombinant Cm NAGase. Next, three organic solvent systems, including LiCl/dimethylacetamide, CaCl2 /Methanol, and hexafluoroisopropanol were applied to treat chitin, resulting in 4.90–8.21-fold improvement of hydrolysis efficiency compared to raw chitin. The decreased crystallinity and nanofiber size structure without deacetylation, confirmed by SEM, FTIR, XRD, and EA, aided in the increased efficiency. Finally, yields of 20.97 mM, 34.50 mM, and 32.53 mM of GlcNAc with a purity of 96% were respectively obtained from 10 g/L of CLD, CHP, and CCM in 24 h.